Performance Evaluation of Accredited Social Health Activist under National Rural Health Mission in Mysore District: A Cross-Sectional Study - Srinivas Nagaraj; Santosh Achapppa; Prashantha Bettapa; B Prakash (Medsci Publications, 2017)
Introduction: National Rural Health Mission (NRHM) came to address the health needs of rural population, especially the vulnerable section of the society. One of the key components of the NRHM is to provide every village in the country with a trained female community health activist or Accredited Social Health Activist (ASHA).  With this background this study was conducted with objectives to assess the performance of ASHA workers and to assess the factors influencing their performance in Mysore District. Methodology: A cross-sectional study was conducted between January 2014 to July 2014, in three taluks of Mysore District using multistage random sampling and PHC's were selected to get ASHA workers of sample size 220(n =Z2pq/L2, With design effect of 2 and 10% cases as non-respondents). A pre tested and structured questionnaire was used. Results: Among 216 ASHA workers who participated in the study, 126(58.3%) were well performing based on JSY performance and 129(59.7%) were performing better in PNC visits whereas, 143(66.2%) were underperforming based on the immunisation coverage. Conclusions: As ASHA worker plays a key role in programme implementation at gross root level, Job performance of these workers plays a vital role in success of the program.